2021
DOI: 10.4038/sljch.v50i4.9891
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of snake bite in children at a tertiary care centre in South India

Abstract: Introduction: Snake bite is an important public health problem in the rural tropics, resulting in envenomation and death. Objectives:To study the clinical profile of snake bite at a tertiary care centre in South India, estimate its case fatality rate and estimate the prevalence of complications in children with snake bite.Method: This was a retrospective, observational descriptive record based study conducted in a Medical College in South India between May 2011 and April 2020.Results: A total of 160 snake bite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[ 6 ] Our study found that snake bite was more commonly seen in males with a ratio of 2.3:1, similar to other studies. [ 3 , 7 , 8 ] This is probably because of more outdoor activities amongst males compared to female children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Our study found that snake bite was more commonly seen in males with a ratio of 2.3:1, similar to other studies. [ 3 , 7 , 8 ] This is probably because of more outdoor activities amongst males compared to female children.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to other studies. [ 7 ] This difference is due to delays in referral and seeking treatment, religious beliefs, and herbal remedies available locally in rural areas before coming to a tertiary care centre.…”
Section: Discussionmentioning
confidence: 99%